Descriptions of the developmental stages of Cafius nauticus (Fairmaire) (Coleoptera: Staphylinidae: Staphylininae), with comments on its biology - Cai, Yu-Jie; Tang, Liang (Zootaxa, 2022)
The egg, two larval instars (L1, 2) and pupa of Cafius nauticus (Fairmaire) are described for the first time. Detailed external structures of the mature larvae are re-described. The structural features of each instar are illustrated as well as the adults. Biological information including intra- and interspecific interactions and ecological preferences are recorded for the first time.